1998
DOI: 10.1063/1.477511
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of spin-spin and spin-lattice relaxation times of paramagnetic nitrogen defects in diamond

Abstract: Spin-lattice relaxation times of P1 centers in a suite of two natural type Ib, two synthetic type Ib, and one natural type Ia diamonds were measured at 9.6 GHz as a function of temperature in the range 300 K>T>4.2 K. An analysis of the results revealed that for three of the diamonds (two synthetic type Ib and the natural type Ia) spin-orbit phonon-induced tunneling is the main relaxation mechanism. In the case of the Ia diamond cross-relaxation takes place between P1 and P2 centers. In the natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
48
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 19 publications
6
48
0
Order By: Relevance
“…The obtained fit parameters A 8:0 10 ÿ3 and B 3:5 10 ÿ10 are close to the values found in Ref. [29]. It was, however, noticed that although the fit explains the main trend, there is a significant deviation for several data points.…”
Section: Prl 101 047601 (2008) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 60%
See 3 more Smart Citations
“…The obtained fit parameters A 8:0 10 ÿ3 and B 3:5 10 ÿ10 are close to the values found in Ref. [29]. It was, however, noticed that although the fit explains the main trend, there is a significant deviation for several data points.…”
Section: Prl 101 047601 (2008) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 60%
“…2, T 1 of both centers increases significantly as the temperature is reduced. For the N-V center, T 1 changes from 7:7 0:4 ms to 3:8 0:5 s. For the N center, T 1 increases from 1:38 0:01 ms to 8:3 4:7 s. For the spin-lattice relaxation of the N centers, it was found that a spin-orbit induced tunneling model is the main mechanism [29]. We fit our data to their model given by 1=T 1 AT BT 5 , where A and B are parameters.…”
Section: Prl 101 047601 (2008) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
See 2 more Smart Citations
“…Using a pump-probe technique in the dispersive regime, we measure spin linewidth and relaxation time. The observed temperature independence indicates that internal spin equilibration is dominated by spin diffusion across the mode volume [20] rather than spin-lattice relaxation [21]. Finally, as an initial test of the possible use of sub-ensembles as independent memories, we measure the steady-state depolarization of a sub-ensemble by resonant pumping of another.…”
mentioning
confidence: 99%